2022
DOI: 10.3389/fpsyg.2021.672395
|View full text |Cite
|
Sign up to set email alerts
|

Social and Cognitive Psychology Theories in Understanding COVID-19 as the Pandemic of Blame

Abstract: When faced with adverse circumstances, there may be a tendency for individuals, agencies, and governments to search for a target to assign blame. Our focus will be on the novel coronavirus (COVID-19) outbreak, where racial groups, political parties, countries, and minorities have been blamed for spreading, producing or creating the virus. Blame—here defined as attributing causality, responsibility, intent, or foresight to someone/something for a fault or wrong—has already begun to damage modern society and med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In COVID‐19, the emergence of societal solidarity was evident in many societies across the world (Berrocal et al, 2021 ; Prainsack, 2020 ; Tomasini, 2021 ), however this sentiment was arguably hard to sustain in more individualistic societies (Flynn, 2022 ), and gradually declined in the United Kingdom and Ireland as examples of rule breaking began to emerge through both government rhetoric and news media (Bouguettaya et al, 2022 ; Forester & McKibbon, 2020 ; West‐Oram, 2021 ; Williams, 2021 ). The initial appraisals of solidarity from the public and the government by frontline workers gave them much‐needed hope and served to maintain their resilience in the early phases of the pandemic (Kinsella et al, 2021 ), and workers themselves appear to understand the importance and significance of the solidarity they enact for society in carrying out their work and seeking to protect others around them.…”
Section: Discussionmentioning
confidence: 99%
“…In COVID‐19, the emergence of societal solidarity was evident in many societies across the world (Berrocal et al, 2021 ; Prainsack, 2020 ; Tomasini, 2021 ), however this sentiment was arguably hard to sustain in more individualistic societies (Flynn, 2022 ), and gradually declined in the United Kingdom and Ireland as examples of rule breaking began to emerge through both government rhetoric and news media (Bouguettaya et al, 2022 ; Forester & McKibbon, 2020 ; West‐Oram, 2021 ; Williams, 2021 ). The initial appraisals of solidarity from the public and the government by frontline workers gave them much‐needed hope and served to maintain their resilience in the early phases of the pandemic (Kinsella et al, 2021 ), and workers themselves appear to understand the importance and significance of the solidarity they enact for society in carrying out their work and seeking to protect others around them.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that in some countries, Muslims are to be blamed for the increased prevalence of COVID-19 cases throughout the community ( Jha and Dixit, 2020 ; Rahim, 2020 ), and a similar situation was also faced by Muslims in Malaysia ( Adetunji, 2020 ; Ananthalakshmi and Sipalan, 2020 ). During the pandemic, collective voluntary responses are needed, and this blaming situation may be harmful to subgroups’ willingness to participate in governments’ initiatives ( Bouguettaya et al, 2022 ). Besides, it may also lead to varying consequences, both directly on the COVID-19 response and indirectly by promoting unfavorable and intolerable general social issues ( Bouguettaya et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…During the pandemic, collective voluntary responses are needed, and this blaming situation may be harmful to subgroups’ willingness to participate in governments’ initiatives ( Bouguettaya et al, 2022 ). Besides, it may also lead to varying consequences, both directly on the COVID-19 response and indirectly by promoting unfavorable and intolerable general social issues ( Bouguettaya et al, 2022 ). Thus, the decision to choose Muslims as the study’s respondent was considered an acceptable option.…”
Section: Methodsmentioning
confidence: 99%
“…Amongst vaccinated people and caregivers, many feel that this blame is justified: their attitude increases the risk of contagion, while overburdening the healthcare system. Yet, as Bouguettaya et al (2022) have stressed, blame in a context of pandemics affects relationships, promotes devaluation of caregivers, and prompts discrimination: it is thus necessary to account for the emergence of blame, in order to devise alternate responses to vaccine refusal. This is crucial in France where vaccine acceptance rates have been very low ( Sallam, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…While “media framing” of the blame is a reality ( Court et al, 2021 ; Bouguettaya et al, 2022 ), it is the inconsistency of VS and AV that vaccinated people and doctors put forward when explaining the blame of selfishness. They perceive VS and AV to rely heavily on the responsibility of vaccinated people to protect themselves and others, while at the same time denying the relevance of the vaccine.…”
Section: Introductionmentioning
confidence: 99%